2020
DOI: 10.1007/s11783-020-1228-y
|View full text |Cite
|
Sign up to set email alerts
|

An efficient resin for solid-phase extraction and determination by UPLCMS/MS of 44 pharmaceutical personal care products in environmental waters

Abstract: A hydrophilic resin (GCHM) was facile synthesis and characterized. • Average absolute recovery of GCHM (75.6%) performs better than Oasis ® HLB. • Detection limits of method (SPE-UPLC-MS/MS) ranged between 0.03 and 0.6 ng/L. • 22 PPCPs were determined in environmental waters ranging from 0.5 to 1590 ng/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Different studies applied attractive modifications to these traditional cartridges, to obtain the best recoveries for a large spectrum of compounds. Zhu et al [52] developed, characterized and tested a hydrophilic resin based on poly(N-vinyl pyrrolidone-co-divinylbenzene) (NVP-co-DVB) that improved the average absolute recovery for 44 PPCPs, with respect to the use of HLB sorbents. Alternatively, Caban et al [62] studied the modification of the columns through the application of additional sorbents on top of a polymeric HLB column to improve the SPE of 15 analytes (pharmaceuticals and estrogens) from water.…”
Section: Sorbents and Formatsmentioning
confidence: 99%
“…Different studies applied attractive modifications to these traditional cartridges, to obtain the best recoveries for a large spectrum of compounds. Zhu et al [52] developed, characterized and tested a hydrophilic resin based on poly(N-vinyl pyrrolidone-co-divinylbenzene) (NVP-co-DVB) that improved the average absolute recovery for 44 PPCPs, with respect to the use of HLB sorbents. Alternatively, Caban et al [62] studied the modification of the columns through the application of additional sorbents on top of a polymeric HLB column to improve the SPE of 15 analytes (pharmaceuticals and estrogens) from water.…”
Section: Sorbents and Formatsmentioning
confidence: 99%
“…However, besides the pH effect, it was found that the NOM between (6-18) kDa exhibited higher impacts on the adsorption at neutral and high pHs, as the influence of NOM between (6-18) kDa and (18-60) kDa became more evident at pH 3 (the adsorbed concentration was dropped by 66% and 86%, respectively). Using an equation of R min = (3V/4) 1/3 (where R min and V represent the size in nm and MW in Da, respectively) for the NOM size prediction [41], the size ranges of NOM between (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) kDa and (18-60) kDa were (1.2-1.7) and (1.7-2.6) nm, respectively. Our BET analysis indicated that ~90% of the pore sizes of GO-Fe 3 O 4 -2.5 ranged from 1 to 7 nm (Figure 3A).…”
Section: Selective Adsorption By Pore Size Tuning: Isothermmentioning
confidence: 99%
“…Over 80% of the intake dose can be excreted from the human body after metabolism [ 15 ]. As a result, PRO is frequently detected in rivers [ 16 , 17 ] and estuaries [ 18 ] in concentrations of up to 142 ng/L.…”
Section: Introductionmentioning
confidence: 99%